Sociological Problems faced by Farmers due to Dyeing Industrial Effluents in the Noyyal River basin of Tamil Nadu - A. Anitha Pauline; C. Karthikeyan (Journal of Agricultural Extension Management, 2016)
The study mainly focuses on sociological problems faced by farmers due to dyeing industrial pollution. The study was conducted in Tiruppur and Erode districts of Tamil Nadu during the year 2015. A sample size of 90 farmers from each category viz., affected and unaffected areas were considered for the study. Totally 180 farmers were selected as respondents for the study. The selection of affected and unaffected areas was based on their distance from industrial zones and their well water quality standards. In the affected area, all the respondents had experienced major problems such as 'hike in wages of agricultural labour' (100%), 'fear of pollution problems influenced the division of family land and its disposal for other purposes' (100%), 'contamination of drinking water source by industrial effluents' (100%), 'deterioration in quality of drinking water in its taste' (100%), reduced availability of labour for agricultural purpose' (95.55%), 'more prevalence of eye, nose and throat irritations, head ache and viral fever' (100%) and 'increased health care expenditure' (91.11 %) were reported by farmers in the Noyyal river basin